Beneficial effects of physical exercise on the exocrine pancreas - Yoko Shiroya; Kumiko Minato (Japanese Society of Physical Fitness and Sports Medicine, 2015)
The pancreas is a retroperitoneal organ critically important for intestinal digestion. Most of the pancreas consists of exocrine glands that synthesize and secrete a great majority of digestive enzymes into the pancreatic duct tributaries and on into the duodenum. It also contains important endocrine glands that produce hormones such as insulin, glucagon, and somatostatin, thus also regulating nutrition and gastrointestinal function. Since the exocrine pancreas serves a central and essential role in the digestive process, its dysfunction may result in malabsorption and malnutrition. Previous studies have shown that exocrine pancreatic dysfunction could be induced by various physical conditions such as obesity, diabetes, and aging. In addition, food consumption and dietary components have been reported to affect pancreatic enzyme synthesis and secretion. However, little is known about the effects of physical exercise on the function of the exocrine pancreas. This review focuses on the effects of physical exercise on functional and ultrastructural alterations in the exocrine pancreas. Furthermore, the importance of physical exercise on exocrine pancreas dysfunction is discussed.